Effects of leaf extracts of Myrcia guianensis (Aubl.) DC. on growth and gene expression during root development of Sorghum bicolor (L.) Moench - Franco, D. M.; Saldanha, Luiz L.; Silva, E. M.; Nogueira, F. T. S.; Dokkedal, A. L.; Santos, Catarina dos [UNESP]; Almeida, Luiz Fernando Rolim de (My University, 2015)
The allelopathic potential of leaf extracts from the medicinal plant Myrcia guianensis (Aubl.) DC. was studied in Petri dish bioassays on sorghum and determined the seed germination, germination rate index (GRI), root growth, secondary root number, the genes involved in root development (SHR, PHB, PHV and REV) and microRNA 166 that regulates these genes. The hydroalcoholic extract was more inhibitory than methanol extract (moderate inhibition) and aqueous extract at 25 and 100% concentration were least inhibitory. Application of higher dose of hydroalcoholic M. guianenesis leaf extracts on sorghum seeds, inhibited the root development and changed the expression of SHR and PHB genes and microRNA 166. This suggested that the expression of these genes could be indicator of allelopathic potential for inhibition of root development in sorghum.